(untitled) (IAHS Medical Journal, 2026)
Background: Anorectal Malformations (ARM) are among the most common congenital anomalies encountered in paediatric surgery. Vestibular anus represents a low-type ARM. Early diagnosis and timely intervention can significantly improve outcomes. Case Presentation: We present the case of a female neonate with vestibular anus associated with imperforate anus, identified on the first day of life. Definitive management was performed at eight months of age using a modified Anterior Sagittal Anorectoplasty (ASARP) technique. The postoperative course was uneventful. Conclusion: This report highlights the clinical presentation, diagnostic evaluation, surgical management and favourable postoperative outcome of vestibular anus in a female patient. IAHS Medical Journal Vol 8(2), December 2025; 87-90